1985
DOI: 10.1530/acta.0.1100135
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of angiotensin II (A-II) by human placental subcellular fractions, pregnancy sera and purified placental aminopeptidases

Abstract: Abstract. The degradation of angiotensin II (Asp1-Arg2-Val3-Tyr4-Ile5-His6-Pro7-Phe8: A-II) by human placental particulate and soluble fractions, pregnant and non-pregnant sera, and highly purified placental enzymes such as placental leucine aminopeptidase P-LAP (microsomal), retroplacental serum P-LAP (soluble), aminopeptidase A and post-proline endopeptidase, was studied by measuring liberated amino acids by high performance liquid chromatography. Placental particulate and soluble fractions degraded A-II alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Over the course of many years, the nature of so-called 'angiotensinase' has been stud ied [16][17][18][19]. It has been widely accepted that 'angiotensinase' is not a single enzyme but includes many enzymes such as aminopepti dase M (EC 3.4.11.2), cystine aminopepti dase (EC 3.4.11.3) and aminopeptidase A (EC 3.4.11.7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of many years, the nature of so-called 'angiotensinase' has been stud ied [16][17][18][19]. It has been widely accepted that 'angiotensinase' is not a single enzyme but includes many enzymes such as aminopepti dase M (EC 3.4.11.2), cystine aminopepti dase (EC 3.4.11.3) and aminopeptidase A (EC 3.4.11.7).…”
Section: Discussionmentioning
confidence: 99%
“…cleaves the N-terminal Asp' of angiotensin II in vitro [19]. Furthermore, we have recently observed that AAP shows a drastic hypoten sive effect in spontaneously hypertensive rats [20].…”
mentioning
confidence: 99%
“…Recently we showed that these hor mones can be degraded with placental and pregnancy serum aminopeptidases including the present enzyme in vitro [27,28]. They may function in the intracellular protein turnover or in the metabolism of biologically active peptides in normal and pathologic conditions.…”
Section: Discussionmentioning
confidence: 90%
“…In turn AngI is a substrate for angiotensin-converting enzyme (ACE: EC3.4.15.1), a zinc metalloprotease that hydrolizes the carboxyl terminal dipeptide histadine-leucine (His-Leu) to form AngII [10]. AngII is converted to AngIII by APA that cleaves the aspartic acid (Asp) residue at the N-terminal [11][12][13][14]. Fig.…”
Section: Formation Of Angiotensin Ligands and Their Receptorsmentioning
confidence: 99%